Importance of Sensor Readings and Its Secured Delivery in Internet of Things - Gupta, Kratika; Kumar, Ashwani; Rasal, Suraj; Rasal, Varsha S (International Journal of Computer Sciences and Engineering, 2025)
Internet of things plays a vital role in the human life. Raspberry Pi is one of the widely used IoT based module. IoT includes information delivery as important property aspect. In this paper importance of sensor reading is highlighted. Sensor readings are important values on which further values may depend. Like IoT appliances used in chemical , pharmaceutical or agricultural industries. In such industries, sensor reading values are important. This paper proposed the importance of sensor value delivery and its impact. IoT based water plantation is considered to explain how sensor values are used to perform certain tasks using raspberry pi module.